The Relationship Of Gentamycin Antibiotic Exposure To: Escherichia Coli Bacteria Resistant To Antibiotic Gentamycin And Escerichia Coli ESBL In Vitro - Kusumawati, Diah Retno (Jurnal Medis Islam Internasional, 2021)
Background: The development of bacteria that have been resistant to antibiotics can complicate the treatment process. Either causes of antibiotic resistance is inappropriate use of antibiotics. Gentamycin is an aminoglycoside-derived antibiotic which its role is very significant for gram-negative bacteria. Repeated use of gentamycin antibiotics can cause changes the effectiveness of gentamycin so that non ESBL-Gentamycin susceptible Escherichia Coli will change into ESBL-Gentamycin resistant Escherichia coli. Objective: This study aims to prove that repeated exposure to Gentamycin in vitro will change non ESBL-Gentamycin susceptible Escherichia Coli into ESBL Gentamycin resistant Escherichia Coli. Methods: This was an experimental study with 30 samples of non ESBL-Gentamycin susceptible Escherichia coli isolates identified from the Phoenix. Non ESBL- Gentamycin susceptible Escherichia coli was tested by giving exposure to Gentamycin for 14 days, then ESBL screening was tested by Cefotaxime exposure to the results of Gentamycin exposure. Result: There were 4 isolates of Escherichia coli which experienced changes in phenotype into Gentamycin resistant Escherichia coli. The rest of it still susceptible to Gentamycin on days 2, 4 and 10. Furthermore, the Escherichia coli isolates were both susceptible to Gentamycin and those that had phenotypic changes become resistant to Gentamycin after exposed to Cefotaxime as an ESBL screening. There are 8 (26.7%) isolates that are still susceptible to Cefotaxime and 18 (60%) isolates that have been transformed into ESBL-Gentamycin susceptible Escherichia coli. Isolates of 4 (13.3%) Gentamycin-resistant Escherichia coli are then exposed to Cefotaxime and obtained all isolates is resistant to Cefotaxime. Conclusion: Repeated exposure of Gentamycin for 14 days in vitro was not significantly related to the phenotypic changes of non ESBL-Gentamycin susceptible Escherichia coli isolates into ESBL-Gentamycin resistant Escherichia coli (P = 0.550, Phi=0.237). Keywords: Escherichia coli, Susceptible, Resistant, Gentamycin, ESBL